Effect of Intracanal Post Space Treatments on Push-Out Bond Strength of Fiber Posts to Root Dentin - Hamid Kermanshah; Behnam Bolhari; Faraz Sedaghat; Ladan Ranjbar Omrani (Tehran University of Medical Sciences, 2017)
Objectives: The main disadvantage of fiber posts is their low bond strength to root canal wall. The aim of the present study was to assess the effect of different root canal post space treatments on push-out bond strength of fiber posts to root dentin. Materials and Methods: After post space preparation in 40 endodontically treated human premolars, the teeth were randomly divided into four experimental groups: Group 1: control group, group 2: Endsolv R, group 3: ultrasonic cleaning, group 4: Clearfil Repair. Afterwards, the posts were bonded with Panavia F 2.0 bonding cement. The bond strength of fiber posts to root canal wall in the middle part of canal was evaluated following thermocycling using push-out test. Data were analyzed using one-way ANOVA and Tamhane's multiple comparisons test. The failure mode of each group was determined under a stereomicroscope. Results: There was a significant difference in the mean push-out bond strength among the groups (P<0.05). The lowest bond strength was noted in the control group. The control group had significant differences with ultrasonic and Clearfil Repair groups (P<0.05). The bond strength of Endsolv R group increased; however, it was not significant (P>0.05). Conclusions: It seems that ultrasonic cleaning and Clearfil Repair can modify the root canal wall and significantly increase the bond strength of fiber posts.